The burden of HIV/AIDS in Ethiopia: Unveiling 30 years of trends in incidence, mortality, and disability—insights from the Global Burden of Disease study (1990–2021) - Tegene Atamenta Kitaw; Molla Azmeraw; Biruk Beletew Abate; Befkad Derese Tilahun; Alemu Birara Zemariam; Addis Wondmagegn Alamaw; Abebe Merchaw Faris; Addisu Getie; Molalign Aligaz Adisu; Tesfaye Engdaw Habtie; Melesse Abiye Munie; Ribka Nigatu Haile (PLoS ONE, 2025)
Background Over the past three decades, Ethiopia has witnessed a dynamic shift in the burden of HIV/AIDS, a public health crisis that has profoundly impacted communities nationwide. While significant strides have been made in combating the disease, evolving trends in incidence, mortality, and disability reveal the complexity of progress. The insights drawn from the Global Burden of Disease Study (1990–2021) offer a comprehensive perspective on the successes and ongoing challenges. Understanding these trends is critical for refining public health strategies and achieving more equitable health outcomes. This study delves into the data, unveiling key findings that inform future policies and interventions. Methods This study used data from the 2021 Global Burden of Disease Study (1990–2021) to evaluate HIV/AIDS incidence, mortality, and DALYs in Ethiopia. The dataset, including age-standardized rates and 95% uncertainty intervals, was obtained from the Global Health Data Exchange (GHDx). Statistical analyses included Joinpoint regression to identify trend shifts and calculate the Annual and Average Annual Percentage Change over time, with significance determined at a p-value of 0.05. Geographic variations were visualized using ArcGIS Pro, highlighting regions with varying HIV burdens. The comprehensive methodology adhered to GATHER guidelines for transparent reporting. Results In 2021, 715,839 individuals (95% UI: 568,889.58–914,511.59) were living with HIV in Ethiopia, and 839,819.31 DALYs (95% UI: 620,558.56–1,154,483.92) were recorded. There was a significant decline in the age-standardized HIV incidence rate, from 175.4 per 100,000 in 1990 to 22.4 per 100,000 in 2021, with an average annual percentage change (AAPC) of -6.64% (p <  0.001). Mortality rates rose from 14.2 per 100,000 in 1990 to 79.7 in 2000 but decreased to 13.6 by 2021, with an AAPC of -1.19%. DALYs peaked in 2010 at 1,695.1 per 100,000 and declined to 770.9 per 100,000 in 2021, with an AAPC of -1.43%. Higher incidence (28.1) and mortality (17.7) were observed in females compared to males (16.7 and 9.6). The Gambela region reported the highest burden, with an incidence rate of 176.3 per 100,000, a mortality rate of 78.4 per 100,000, and 4,220.7 DALYs per 100,000. Conclusion Ethiopia accounts for 1.8% of the global HIV/AIDS prevalence. While significant progress has been made in recent years, sustained efforts are necessary to further reduce the burden of the disease. The disproportionate impact on females and the Gambela region underscores persistent disparities in prevention and care. To achieve equitable health outcomes across the country, it is crucial to implement targeted, evidence-based interventions that address these gaps in the HIV/AIDS response.